Intensidades luminosas e profundidade de Semeadura na emergência e desenvolvimento de espécies de plantas daninhas - Souza, Guilherme Sasso Ferreira de [UNESP] (2014)
This study aimed to evaluate the effect of sowing depth and light intensity on germination and growth of Acanthospermum australe, Urochloa decumbens, Urochloa humidicola, Urochloa plantaginea, Senna occidentalis, Senna obtusifolia, Cenchrus echinatus, Desmodium tortuosum, Euphorbia heterophylla, Ipomoea grandifolia, Ipomoea quamoclit, Raphanus raphanistrum and Sida rhombifolia. Each species represents an experiment, which conducted in a completely randomized design, with four replications. The treatments were arranged in a 6x4 factorial design, with the first factor corresponding to six different sowing depths (0.5, 1.0, 2.0, 4.0, 8.0 and 12.0 cm) and the factor B to four light intensities (100%, 70%, 50% and 30% of the solar light intensity) obtained by the use of agricultural nets. Seed emergency was evaluated daily for a period of 26 days from sowing to obtain the germination percentage and the EVI (Emergence Velocity Index). The plant height and blooming time were also recorded, in addition to the dry mass of plants at flowering. The relevant characteristics of each light intensity treatment, such as air temperature, relative humidity and soil temperature at depths studied were verified The photosynthetically active radiation was also quantified through the use of a quantometer. All results were submitted to variance analysis by F Test and the treatment means were compared by Tukey test at 5% of probability. The plants of U. decumbens, U. plantaginea, C. echinatus, A. australe, S. occidentalis, S. obtusifolia, R. raphanistrum, I. grandifolia, I. quamoclit and E. heterophylla emerged in sowing depth up to 12.0 cm, while plants of U. humidicola and D. tortuosum did not emerged at 12.0 cm depth with a light intensity lower than 50% and 70%, respectively. Plants of S. rhombifolia did not emerge in 12.0 cm depth on full light condition. Shading increased the time to flowering of all species evaluated ...